Влияние метеорологических условий на динамику фенологического развития Anemonoides ranunculoides (L.) Holub - Зубцова, Т.В.; Остапко, В.М.; Муленкова, Е.Г. (Промышленная ботаника, 2002)
The results of many year phenologic observations of Anemonoides ranunculoides (L.) Holub are cited. Alterations in blossom duration depending on falls amount have been revealed. The graphs on dynamics of phenologic development are given, constructed basing on the data of phenologic observations, converted to the row of continuous numbers depending on mean air temperature and precipitation.